Effect of Propolis supplementation on the redox state of human serum Albumin during high-intensity Kendo training - Imai, H.; Era, S.; Hayashi, T.; Negawa, T.; Matsuyama, Y.; Okihara, K.; Naskatsuma, A.; Yamada, H. (Advances in Exercise and Sports Physiology, 2005)
Human serum albumin (HSA) is a mixture of human mercapt- (HMA, reduced form) and nonmercaptalbumin (HNA, oxidized form), and is known to be one of the major extracellular scavengers for reactive oxygen species. Using a high-performance liquid chromatographic (HPLC) system with an ES-502N column, we studied the redox state of HSA for male Japanese fencing ("kendo") athletes (n=11) before and after an intense kendo training camp for 4 days. In order to clarify the antioxidative effect of propolis supplementation on the HSA redox state during camp, subjects were divided into two groups (placebo group, n=5; propolis group, n= 6). A double blind test was utilized. The propolis used in this study was a product of Brazil (daily amount of propolis was 787.5 mg). During camp, the observed decrease in the mean values of [HMA/(HMA+HNA)] (f(HMA)) in the placebo group was significant (76.8+/-1.66% before and 63.0+/-2.29% after camp; P<0.05). Similarly, those values for the propolis group were also significant (77.0+/-0.94% before and 70.5+/-1.51% after camp; P<0.05). For the propolis group, however, the degree of the decrease in the f(HMA) value was significantly small compared with that of the placebo group (P<0.05). In addition, the change in the f(HMA) value of the propolis group during the training camp was roughly within the normal range of that of healthy male subjects previously reported (73.2+/-2.34%). These findings suggest that propolis may be an effective supplement to improve the redox state of HSA for kendo athletes in repetitive and highly intensive training camps.